Grasp Tight the Old Ways : Selections from the Klamer Family Collection of Inuit Art - Blodgett, Jean; The Winnipeg Art Gallery, Winnipeg; Field Museum of Natural History, Chicago (Toronto : Art Gallery of Ontario, 1983)
Angaktaaryuag, Joseph ; Anguhadluq, Luke ; Aqiggaaq, Irene ; Iksiktaaryuk, Luke ; Kigusiuq, Janet ; Kukiiyaut, Myra ; Noah, William ; Oonark, Jessie ; Pukingrnak, Nancy ; Sivuraq, Thomas ; Tookomme, Simon ; etc.
Grasp Tight the Old Ways : Selections from the Klamer Family Collection of Inuit Art, Art Gallery of Ontario, Toronto, May 28 - July 31, 1983 ; The Winnipeg Art Gallery, Winnipeg, November 10, 1983 - January 2, 1984 ; Field Museum of Natural History, Chicago, February 27 - May 27, 1984 ; etc.
English
kunstcatalogus